2022
DOI: 10.1038/s41598-022-23606-x
|View full text |Cite
|
Sign up to set email alerts
|

Sensing whales, storms, ships and earthquakes using an Arctic fibre optic cable

Abstract: Our oceans are critical to the health of our planet and its inhabitants. Increasing pressures on our marine environment are triggering an urgent need for continuous and comprehensive monitoring of the oceans and stressors, including anthropogenic activity. Current ocean observational systems are expensive and have limited temporal and spatial coverage. However, there exists a dense network of fibre-optic (FO) telecommunication cables, covering both deep ocean and coastal areas around the globe. FO cables have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Ocean-bottom DAS can be used for monitoring low-frequency ocean-bottom vibrations corresponding to OSGWs and, hence, ocean swells. In this section, we elaborate our detailed analysis of the same DAS data for storm monitoring as presented in Landrø et al (2022). Figure 9 shows spectrograms from three individual DAS recording channels at different water depths and distances from the shore.…”
Section: Ocean Wave Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…Ocean-bottom DAS can be used for monitoring low-frequency ocean-bottom vibrations corresponding to OSGWs and, hence, ocean swells. In this section, we elaborate our detailed analysis of the same DAS data for storm monitoring as presented in Landrø et al (2022). Figure 9 shows spectrograms from three individual DAS recording channels at different water depths and distances from the shore.…”
Section: Ocean Wave Monitoringmentioning
confidence: 99%
“…DAS in submarine fiber-optic cables can measure pressure fluctuations at the ocean bottom, originating from a variety of sources (Landrø et al, 2022). DAS in ocean-bottom telecommunication fiber-optic cables can detect ocean surface gravity waves, microseisms and earthquakes (Lindsey et al, 2019;Sladen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to seismic monitoring, fiber sensing technologies have been applied to understand ocean dynamics and detect underwater phenomena. Lindsey et al 5 demonstrated the use of dark fiber distributed acoustic sensing for mapping seafloor faults and monitoring ocean dynamics, while Landrø et al 6 utilized arctic fiber optic cables for sensing whales, storms, ships, and earthquakes, proving the versatility of fiber sensing in harsh environments. Skarvang et al 7 presented observations of local small magnitude earthquakes using state-ofpolarization monitoring in a passive arctic submarine communication cable, highlighting the potential of polarization-based sensing techniques in seismic monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Applying distributed sensing to the telecommunication fiber network can leverage the communication cable for ocean monitoring. In addition to the intrinsic function of optical fibers for data transmission across oceans, optical fiber sensing technology can monitor the ambient environment near the fiber across oceans 17 , 18 . For instance, optical fiber distributed acoustic sensing (DAS) can achieve seismological data collection 15 , 19 , geophysical monitoring 20 , earthquake wavefields sensing 21 , and other ocean monitoring data collection applications 16 .…”
Section: Introductionmentioning
confidence: 99%